Assessing Bank Competition within the East African Community - Sanya, Sarah (IMF Working Papers; Working Paper ;, 2012)
This paper is an empirical analysis of competitiveness in the banking system of four out of the five East African Community (EAC) countries2. The results show that the degree of competition is low due to a combination of structural and socio-economic factors. By way of preview, the analysis ranks the countries in terms of banking sector competitiveness in the following order: Kenya, Tanzania, Uganda and Rwanda.